L’écriture de Maurice Renard, en tension entre extrapolation scientifique et figuration littéraire - Simon Bréan (ReS Futurae)
Theorizing about the very genre he’s trying to promote, Maurice Renard provides the “merveilleux-scientifique” (scientific marvelous, 1909), then the “roman d’hypothèse” (hypothesis novel, 1925) with great ambitions. However his own writing strikingly exceeds his initial program. Renard’s works abound in incitative literary devices and strategies, that may weaken scientific extrapolation : the use of fictional artefacts, following the tradition of the Fantastique, of humor, of characters and situations coming from popular serials, of eroticism. Nevertheless, the tension between these varied aspects only adds to the coherence of Maurice Renard aesthetics. This paper aims at showing how the writer of the “merveilleux-scientifique” gives life to his hypotheses, focusing on Le Docteur Lerne, Le Péril bleu, Les Mains d’Orlac, « L’Homme truqué », Un homme chez les microbes, and Le Maître de la lumière.